DAKWAH DALAM MASYARAKAT PLURALIS - Efendi P. (IAIN Palopo, 2009)
Da’wah is an effort to invite people through the right way. It is to get reward from the God. Therefore, da’wah is an obligation which can’t be denied by each adult Moslem. So, to invite someone in the right way, the preacher (da’i) must do through the right way too. In facing of various society, the need of a wise and persuasive da’wah is a necessary.